Remittance inflow and the brain drain issue in Malaysia / Fauziana Fauzi @ Mat Rawi and Marziah Mokhtar - Fauzi @ Mat Rawi, Fauziana; Mokhtar, Marziah (Universiti Teknologi MARA, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2018)
This paper intends to study the impact of remittance inflow on the Malaysian economy. It was found that recipient countries benefited from the inflow of remittance economically, financially and socially. Malaysia is one of the remittance recipient countries besides Philippines, Mexico and India. In the Malaysian context, most of the remittances come from skilled workers or professionals. Although remittances received will have positive effects on the Malaysian economy, it also creates brain drain issues due to the outflow of high skilled workers and professionals to other countries. As reported, more than two million people have emigrated since Malaysia’s independence in 1957 resulting in increase in remittances which shows the inflow of capital. This is only the short run impact. In long term, the country might face ‘double whammy’ on decrease in the remittance inflow.